Recht auf Gesundheit, citizenship und die Moralökonomie einer sozialmedizinischen Versorgung vulnerabler Bevölkerungsgruppen in Rio de Janeiro - Lidola, Maria (My University, 2018)
In the course of the 2000s, primary healthcare-based family clinics were established throughout Rio de Janeiro’s favelas in order to guarantee the Brazilian Constitutional Right to Health, especially for vulnerable populations. The underlying Family and Community Health Program aimed to not only incorporate these populations into public health care but also to transform their conceptions, practices and values regarding health and illness accordant to the Brazilian social medicine approach. But as in other resource poor settings of primary health care, this transformative process was faced with dissatisfaction on the local ground, by the patients as well as by the medical staff. The paper takes a closer look at this scenario of transfiguration by reflecting on the role of differentiated citizenship and vulnerable subjectivities of the favela population within the underlying moral economies of social medicine. Therefore, the paper traces back the historical overlapping of urban social inequality, the Brazilian Right to Health approach and local forms of citizenship claims of the urban marginalized population. The concept of transfiguration will offer an analytic lens to understand this process of transformation in its inconstancy, encompassing the people involved and their subjectivities, their practices of subjectivation but also resistance and agency, their normative expectations and lived experiences.
The Right to Health, Citizenship and the Moral Economy of Social Medicine in Rio de Janeiro's Favelas
Keywords: Right to Health, Social Medicine, Brazil, Citizenship, Favela; 300